Lower white blood cell counts in elite athletes training for highly aerobic sports - Horn, P. L.; Pyne, D. B.; Hopkins, W. G.; Barnes, C. J. (European Journal of Applied Physiology, 2010)
White cell counts at rest might be lower in athletes participating in selected endurance-type sports. Here, we analysed blood tests of elite athletes collected over a 10-year period. Reference ranges were established for 14 female and 14 male sports involving 3,679 samples from 937 females and 4,654 samples from 1,310 males. Total white blood cell counts and counts of neutrophils, lymphocytes and monocytes were quantified. Each sport was scaled (1-5) for its perceived metabolic stress (aerobic-anaerobic) and mechanical stress (concentric-eccentric) by 13 sports physiologists. Substantially lower total white cell and neutrophil counts were observed in aerobic sports of cycling and triathlon (~16% of test results below the normal reference range) compared with team or skill-based sports such as water polo, cricket and volleyball. Mechanical stress of sports had less effect on the distribution of cell counts. The lower white cell counts in athletes in aerobic sports probably represent an adaptive response, not underlying pathology.